Post-transplant lymphoproliferative disorders after allogeneic hematopoietic stem cell transplantation: a case report, meta-analysis, and systematic review - You-yuan Su; Ya-fei Yu; Zhen-yu Yan; Ya-jing Zhao; Jian-wei Lou; Feng Xue; Miao Xu; Qi Feng; Xue-bin Ji; Xiao-yuan Dong; Wen Wang; Chuan-fang Liu; et al. (BMC, 2024)
Abstract Background Post-transplant lymphoproliferative disorders (PTLD) are rare but severe complications that occur after solid organ or allogeneic hematopoietic stem cell transplantations (allo-HSCT), with rapid progression and high mortality. Primary central nervous system (CNS)-PTLD are rarely recognized histo-pathologically. In addition, the diagnostic value of the Epstein-Barr virus (EBV) DNA copies in CNS-PTLD remains poorly understood. Objectives We herein report a case of monomorphic EBV-associated CNS-PTLD (diffuse large B-cell lymphoma, DLBCL) after allo-HSCT and perform a meta-analysis to assess the efficacy of PTLD treatment strategies in recent years. Methods We present the case report covering clinical manifestations, diagnosis, treatment, and outcomes of a patient with primary CNS-PTLD. Additionally, we include a systematic review and meta-analysis of the clinical characteristics of 431 patients with PTLD after allo-HSCT. We evaluate the main treatment options and outcomes of PTLD management, including rituximab, chemotherapies, and autologous or human leukocyte antigen (HLA)-matched EBV-specific cytotoxic T lymphocyte infusion (EBV-CTLs)/donor lymphocyte infusion (DLI). Results The meta-analysis revealed an overall response rate of 69.0% for rituximab alone (95% CI: 0.47-0.84), 45.0% for rituximab plus chemotherapies (95% CI: 0.15-0.80), and 91.0% for rituximab plus EBV-CTLs/DLI (95% CI: 0.83-0.96). The complete response (CR) rate after treatments for PTLD was 67.0% (95% CI: 0.56-0.77). Moreover, the 6-month and 1-year overall survival (OS) rate was 64.0% (95% CI: 0.31-0.87) and 49.0% (95% CI: 0.31-0.68), respectively. Conclusions This case highlighted the urgent need for effective, low-toxic treatment regimens for CNS-PTLD. Our meta-analysis suggested that rituximab combined with EBV-CTLs/DLI could be a favorable strategy for the management of PTLD after allo-HSCT.